2001
DOI: 10.2105/ajph.91.8.1276
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sexual Orientation and Suicide Risk: Evidence From a National Study

Abstract: The findings provide strong evidence that sexual minority youths are more likely than their peers to think about and attempt suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
470
2
12

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 727 publications
(527 citation statements)
references
References 29 publications
35
470
2
12
Order By: Relevance
“…44,45 As discussed in the American Academy of Pediatrics (AAP) statement on sexual orientation and adolescents, 46 boys who are questioning and gay and do not have supportive environments are at increased risk of social isolation, school failure, family conflict, substance abuse, depression, suicide, and stigmatization. [47][48][49][50] Most sexual-minority youth are quite resilient and work through adolescent development issues. Being gay or bisexual or questioning their orientation is not in itself a problem but is a risk factor for exploring other associated risks.…”
Section: Sexual Developmentmentioning
confidence: 99%
“…44,45 As discussed in the American Academy of Pediatrics (AAP) statement on sexual orientation and adolescents, 46 boys who are questioning and gay and do not have supportive environments are at increased risk of social isolation, school failure, family conflict, substance abuse, depression, suicide, and stigmatization. [47][48][49][50] Most sexual-minority youth are quite resilient and work through adolescent development issues. Being gay or bisexual or questioning their orientation is not in itself a problem but is a risk factor for exploring other associated risks.…”
Section: Sexual Developmentmentioning
confidence: 99%
“…LGBT youth (e.g., D 'Augelli, 2002) and lesbian, gay, and bisexual (LGB) adolescents are more likely to attempt and complete suicide than heterosexual adolescents (Russell & Joyner, 2001). While elevated levels of distress and suicidality were once believed to result directly 5 from an LGBT identity, it is now increasingly understood that such difficulties are associated with the adverse social conditions that these youth frequently experience as a result of the stigma that society attaches to their identities.…”
Section: Questioning (Lgbtq) Young People Introductionmentioning
confidence: 99%
“…Results indicated that living in environments that are less supportive of gays and lesbians is associated with greater suicide attempts among LGB youth. Previous studies have documented several factors that increase the risk for suicide attempts among LGB youth, including depression, 7 peer victimization, 4 hazardous alcohol use, 6 and physical abuse by an adult. 21 Even after adjusting for these individuallevel risk factors, the social environment was associated with suicide attempts in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…1 Overall, suicide is the third leading cause of death among youth aged 15 to 24 years, 2 and LGB youth are more likely to attempt suicide compared with their heterosexual peers. This heightened risk for suicide attempts among LGB youth has been replicated across multiple sampling methodologies, including community 3,4 and nationally representative 5,6 surveys, and across different countries. [7][8][9] Research into the underlying factors that may prevent suicide attempts among LGB youth is therefore a critical area for public health.…”
mentioning
confidence: 88%
See 1 more Smart Citation